(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Lab technicians play a pivotal role in managing laboratory data, which is essential for research, diagnosis, and treatment in healthcare and scientific fields. This article explores best practices for handling laboratory data, focusing on data collection, entry, organization, storage, analysis, interpretation, and compliance with data privacy regulations. Key strategies include standardizing data collection procedures, utilizing electronic data entry systems, implementing robust security measures, and collaborating with data analysts. Effective data management enhances research quality, patient care, and regulatory compliance. This article highlights the critical role of lab technicians in ensuring accurate, reliable, and secure management of laboratory data.